Employability Skills of Unaccompanied Immigrant Minors in Canary Islands - Estefanía Alonso-Bello; Lidia E. Santana-Vega; Luis Feliciano-García (Springer, 2020)
Young unaccompanied immigrants have various problems in their professional careers which lead to situations of exclusion and hinder their emancipation. The development and consolidation of employment skills is a necessary condition for the labour integration of this group. This research analyzes the employability skills of unaccompanied young immigrants who must leave the public social protection system when they reach the age of majority. A multiple case study was conducted. The cases were selected: 1) having been in residential care institutions, 2) having been in a job placement program, and 3) are 16-18 years of age. The study data were collected using qualitative and quantitative techniques. Results show that young immigrants have: a) language and socio-emotional difficulties that limit their chances of employability; b) some employability skills that facilitate labour insertion, and c) families which act as a powerful motivator for achieving their goals. We discuss the need to design individual transition plans to help young immigrants overcome their limitations, cope with the transition to adulthood and consolidate their career paths.